Chan : an ancient Maya farming community - Robin, Cynthia (Maya studies., 2012)
The farming community of Chan thrived for over twenty centuries, surpassing the longevity of many larger Maya urban centers. Between 800 BC and 1200 AD it was a major food production center, and this collection of essays reveals the important role played by Maya farmers in the development of ancient Maya society. Chan offers a synthesis of compelling and groundbreaking discoveries gathered over ten years of research at this one archaeological site in Belize. The contributors develop three central themes, which structure the book.